(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The security of computerized systems depends on mechanisms for controlling access. For the enrichment and reinforcement of such systems, a combination of attribute-based access control and blockchain technologies may be deployed. On the other hand, attribute-based encryption may be used to enable secure data management and safeguard access policies. In this research, we have presented innovative blockchain enabled attribute-based access control. Our architecture is the first to integrate different aspects to accomplish many security aspects as well as give partial and total revocation at the same time. The experimental findings and analysis, done utilizing the blockchain of the Ethereum network, proved the superior performance of the suggested method compared to prior research works.